Information literacy skills and attitude towards plagiarism by students of three theological institutions in South-west, Nigeria (2020)
Attitude towards plagiarism of students of theological institutions is considered important as they are expected to be upholders of moral and spiritual values. However, some studies reveal that students of theological institutions have a positive attitude towards plagiarism. This could be a function of their level of information literacy skills. Thus, the main objective of this study is to examine the influence of information literacy skills on the attitude towards plagiarism by students in three theological institutions in South-west, Nigeria. The descriptive survey research design of the correlational type was adopted for this study. The population consisted of 1472 undergraduate and postgraduate students in three theological institutions in South-west, Nigeria. The two-stage random sampling technique was used to arrive at the sample size of 355. Data was collected with the aid of questionnaire. Results showed that the level of information literacy skills of the respondents is also high (overall mean=85.97). Majority of the respondents (𝑥̅=1.41) and (𝑥̅=1.48) also disagreed that it is acceptable to copy word for word from a book or journal without acknowledgement, and that is acceptable to copy from the Internet without citing the source. Also, exactly four-fifths of the respondents (𝑥̅=1.87) agreed that plagiarism is against their ethical values. This depicts a negative attitude towards plagiarism. There is a significant negative relationship between literacy skills and the attitude towards plagiarism by the students (r = -.156**; df = 299; p< 0.05). Part of the recommendations was that the high level of information literacy skills can be strengthened if librarians in collaboration with lecturers continually organise workshops and lectures to build the capacity of the students of theological institutions in information literacy